D03 The effect of exercise on gastrointestinal symptoms and body composition at different phases of the menstrual cycle - Bass, L.; Johnson, K.; Rowland, S.R.; Barrett, J.S.; Dixon, S.; Kennedy, T. (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Women commonly experience bloating, stomach cramps, water retention, and weight gain at the beginning of their menstrual cycle, which cause fluctuations in body composition through extracellular changes, this may affect osmotic pressure, leading to gastrointestinal (GI) symptoms. The aim of this study was to investigate the effect of the menstrual cycle phase on extracellular changes and GI symptoms in females in response to exercise. Seven healthy premenopausal female recreational athletes (maximal O2 consumption: 50 ± 5.8 ml·kg-1) performed two running trials in an experimental crossover design during two distinct phases of the menstrual cycle, early follicular phase (EFP) and the mid-luteal phase (MLP). Each trial consisted of 120 min of running, 60 min at 110% lactate threshold and 60 min at 90%. Determination of cycle was calculated from calendar-based counting and urinary ovulation detection kits. The EFP was determined by self-reporting onset of menses. The day before each trial, participants followed a low FODMAP diet and completed a gastrointestinal symptom rating scale questionnaire. On the morning of the trial, a standard breakfast was consumed, upon arrival at the laboratory, body composition was recorded. Each hour, finger prick samples were taken to measure lactate and ensure performance did not exceed maximum, every 15 minutes, a visual analog scale (VAS) of subjective ratings between 0-10 cm of gut comfort was taken. Data was analysed using mean and standard deviation (subsequent statistical analysis will be conducted if an n = 10 is reached prior to the conference). During exercise, participants experienced a higher prevalence of GI issues throughout the EFP compared with the MLP. The most common complaints reported from the VAS were nausea; EFP 1 ± 1 cm, MLP 0 ± 0 cm. Flatulence; EFP 4 ± 3 cm, MLP 1 ± 1 cm, and stomach cramps; EFP 3 ± 2 cm, MLP 1 ± 1 cm. Total body weight (TBW) differences were noted between the EFP and MLP. TBW EFP pre-exercise was higher than MLP pre-exercise phase EFP pre-exercise: 38.7 ± 2.8 L compared to MLP pre-exercise at 35.8 ±5.5 L. Similar differences were demonstrated with extra cellular water pre-exercise EFP; 16.1 ± 1.1 L MLP; 15.2 ±1.0 L. During the EFP fluid retention is known to be higher than the MLP, and results are as expected. While the data suggests a seemingly minimal variation in Gl symptoms, individually, there appears to be a higher level of difference. More gastrointestinal symptoms were reported during exercise, which is consistent with the findings. There is a slight difference in GI symptoms between the EFP and MLP at this stage, indicating a slight shift in total body water.